Perceptions of ostomized persons due to colorectal cancer on their quality of life - Kimura,Cristilene Akiko (2017)
ABSTRACT Introduction: The significance of the change in the physical body and suffering as the new condition of life of stoma oncological person affect the physical, psychological, social relationships and environment. Objective: To know the perception of quality of life and the interpretation of the biopsychosocial reality of intestinal ostomy due to colorectal cancer clinics of the Ambulatory Care Program ostomy patients of the Health Secretariat of the Federal District, Brazil. Methods: Epidemiological based study, analytical character, with cross-sectional descriptive design with quantitative and qualitative approach in the light of the content analysis. Sample consisted of convenience, included 120 participants. They used the questionnaires sociodemographic, clinical, and WHOQOL-BREF and an individual interview. Data were analyzed by Microsoft Office Excel 2010 and SPSS 20.0 software. Statistical significance was accepted at 5%. Results: Physical Domains, Social Affairs and Environment are correlated with the mean score, statistically significant (p < 0.0001), the content analysis resulted in four categories: Wellness Physical, Psychological Wellness, Wellness and Spiritual Well living Social. Conclusion: Ostomy and colorectal cancer may represent suffered mutilation, loss of productive capacity resulting in the loss of quality of life.